A Novel Augmented Reality-Based Navigation System in Perforator Flap Transplantation — A Feasibility Study. Issue 2 (August 2017) - Jiang, Taoran; Zhu, Ming; Zan, Tao; Gu, Bin; Li, Qingfeng
Abstract : Background: In perforator flap transplantation, dissection of the perforator is an important but difficult procedure because of the high variability in vascular anatomy. Preoperative imaging techniques could provide substantial information about vascular anatomy; however, it cannot provide direct guidance for surgeons during the operation. In this study, a navigation system (NS) was established to overlie a vascular map on surgical sites to further provide a direct guide for perforator flap transplantation. Methods: The NS was established based on computed tomographic angiography and augmented reality techniques. A virtual vascular map was reconstructed according to computed tomographic angiography data and projected onto real patient images using ARToolKit software. Additionally, a screw-fixation marker holder was created to facilitate registration. With the use of a tracking and display system, we conducted the NS on an animal model and measured the system error on a rapid prototyping model. Results: The NS assistance allowed for correct identification, as well as a safe and precise dissection of the perforator. The mean value of the system error was determined to be 3.474 ± 1.546 mm. Conclusions: Augmented reality-based NS can provide precise navigation information by directly displaying a 3-dimensional individual anatomical virtual model onto the operative field in real time. It will allow rapid identification and safe dissection of a perforator in free flap transplantation surgery.